Religious identity and integration of Armenians as an ethnic group in Germany - Sargsyan, Lilit (2022)
Through overall developments and movements, migration has spread throughout the world, causing concurrence and amalgamation of heterogeneous and culturally different societies. Present day societies are culturally even more diverse: individuals live in numerous cultures, speak in various languages, and have different identities. Despite the fact that the movement of Armenians previously existed in Antiquity and the Middle Ages, and Armenians have made numerous networks around the world, the considerable flow of relocation and the modern term of the Armenian Diaspora has developed because of the First World War after the Armenian Genocide in 1915, more explicitly, it comprises mostly individuals who survived the Armenian Genocide. The current research investigates the lives of the Armenian Diaspora in Germany, more specifically, the ones that have moved to Germany from Armenia, Iran, and Turkey. Studying the lives of the Armenian ethnic group in a host society, it discusses the issues of living in heterogeneous societies and cultures, the role that religion plays in the migration and integration context, affiliation and attachment to various cultures, hybrid cultural, religious and social identities: how Armenians perceive themselves and different societies in Germany, what it feels like to be away from their homeland and live in various cultures simultaneously, to what cultures they have a sense of belonging, how they endeavour to retain their ethnic, religious, and cultural identities, what assists them in the integration process, and how they assess their lives in Germany. The research applies three methods: participant observation, semi-structured interview and Stefan Huber’s questionnaire “The Centrality of Religiosity Scale”. Religion plays a vital role in most of the interviewees’ lives, depending on various circumstances, such as a spiritual nourishment, a psychological support, closeness to one’s ethnicity or ethnic group, access to the host society, etc. According to the current research results, the Armenian interviewees in Germany perceive religion as an inseparable part of their culture, since their religious, ethnic, and cultural identities are intertwined and regarded as an inseparable unit: religious identity – Christian, ethnic identity – Armenian, cultural identity – customs and traditions. Christianity is perceived and practiced by the Armenian interviewees as a ‘cultural religion’ for the following reasons. They consider themselves to be Christians, but are not actively engaged in religious rituals or prayers. Christianity played an important role in the history of Armenians since it helped them preserve their ethnic identity and culture throughout history. Christianity has become an inseparable part of their culture since many Armenian customs and traditions are tightly connected to it and play an important role in their ethnic, national, cultural and religious identities. Interestingly enough, even those, who consider themselves to be atheists, conceive Christianity as an indispensable part of the Armenian culture and identity.